Decreasing Chlamydial Reinfections in a Female Urban Population. Issue 12 (December 2021) - Suarez, Jennifer Denise; Snackey Alvarez, Kristin; Anderson, Sharon; King, Helen; Kirkpatrick, Emily; Harms, Michael; Martin, Robert; Adhikari, Emily
Abstract : Background: Chlamydia is the most reported bacterial sexually transmitted infection (STI). The rates of chlamydia rose by 19% between 2011 and 2018. The STI National Strategic Plan (2021–2025), encourages coordinated solutions to address STIs and reduce disparities in disadvantaged populations. Methods: We implemented institutional policy changes, clinical decision support, including a Best Practice Advisory, and defaulted SmartSet with provider and patient education for women's health clinics at a large county health system. The advisory prompted providers to follow best practices when treating Chlamydia trachomatis infections. New C. trachomatis diagnosis cohorts were compared preintervention and postintervention for 6-month reinfection rates and patient and expedited partner treatment (EPT) practices. Results: Five hundred and nineteen women were included in the final analysis. Six-month chlamydia reinfection was lower in the postintervention cohort after adjusting for age (12.3% [26/211] vs 6.5% [20/308], P = 0.02). There was an increase in directly observed therapy of primary patients (17.5% [37/211] vs 77.3% [238/308], P < 0.001), an increase in EPT prescriptions written (4.3% [9/211] vs 79.5% [245/308], P < 0.0001), and a decrease of partners referred out for treatment (61.6% [130/211] vs 5.2% [16/308], P < 0.001) when compared with the control group. The majority of EPT was patient-delivered partner therapy postintervention (3.3% [7/211] vs 69.2% [213/308], P < 0.001). Conclusions: A multifaceted, streamlined approach was effective in changing provider practices in the treatment of C. trachomatis . Increased rates of directly observed therapy for primary patient treatment and increased rates of patient-delivered partner therapy were observed postimplementation in addition to lower 6-month reinfection rates in a public women's health clinic setting. Abstract : A multifaceted, streamlined approach resulted in increased rates of directly observed therapy for primary patient treatment and of patient-delivered partner therapy resulting in lower 6-month reinfection rates.